Translanguaging as a Pedagogical Strategy in EFL Classroom: A case study at Senior High School in Bulukumba Regency - Rahmawansyah Sahib (Universitas Lancang Kuning, 2019)
This study investigates the use of Translanguaging as a Pedagogical Strategy by an EFL teacher in terms of interaction between the teacher and the students in teaching and learning process. It focuses to explore the teacher’s reason for using translanguaging in EFL Classroom, and to explore the benefits of teacher’s translanguaging on students in EFL Classroom. This study applied qualitative method. Two meetings of classroom observations were recorded by using audio recorder. Also, a teacher and ten students were interviewed after the classroom observation. The recordings and interviews were transcribed and analyzed based on the teacher’s reason for using translanguaging in EFL Classroom, and the benefits of teacher’s translanguaging on students. In the research findings there were three kinds of languages namely English as the Foreign language, Indonesia as the national language, and Konjo as the local language that used by the teacher and students in practice of translanguaging during teaching and learning process in EFL Classroom. Therefore, there were four teacher’s reason used translanguaging in EFL Classroom. Furthermore, there were six benefits of teacher’s translanguaging on students in EFL Classroom